Association of Polymorphism (RS1800896) of IL-10 Gene and IL-10 Gene Expression in Ovarian Cancer Patients From Georgia - Balakrishnan, Pavithra; Shah, Jahnvi; Surmava, Sandro; Kvaratskhelia, Eka; Abzianidze , Elene; Vardiashvili, Nino; Kankava, Ketevani (Scripta Medica, 2024)
Background/Aim: Ovarian cancer is one of the most important causes of tumour-associated mortality and morbidity in women. Some genetic alterations, determining predisposition to ovarian cancer have already been identified, but these are mostly syndrome-associated cases, most ovarian tumours are still regarded as sporadic. The aim of this research was to identify new predisposing factors that might increase ovarian cancer risk. Genetic variants of IL-10 gene in patients with ovarian cancer was analysed. Methods: Forty-eight patients with ovarian cancer along with 48 age-matched controls were included in the study. Single nucleotide polymorphism (SNP) genotyping and gene expression assays for IL-10 were performed using TaqMan assay (Thermo Scientific, USA). The selected SNP was rs1800896 upstream of IL-10 gene (IL-10-1082). All statistical analyses were performed by GraphPad Prism 9.3.1 for Mac. Results: The genotype distributions of IL-10 gene polymorphisms among cancer and control groups were all according to the expected Hardy–Weinberg equilibrium. There was no statistically significant difference in frequency of genotypes and alleles between the two study groups (p > 0.05). In another analysis, the samples were grouped according to the polymorphic variant IL-10 (− 1082) A/G. Subjects having the homozygous variant (A/A) had lower IL-10 mRNA levels than those with the homozygous wild (G/G) genotype in both, ovarian cancer patients and controls, p < 0.05. mRNA levels on IL-10 were different among cases and controls (p < 0.05). Patients with ovarian cancer had higher level of mRNA for IL-10. Conclusions: These results support the theory that IL-10 gene expression levels differ in patients with and without ovarian cancer. Polymorphic variant IL-10 (− 1082) A/G couldn’t be confirmed to explain this difference in gene expression levels.